2011
DOI: 10.1007/s11207-011-9827-1
|View full text |Cite
|
Sign up to set email alerts
|

Did the Sun Change Its Behaviour During the Decline of Cycle 23 and Into Cycle 24?

Abstract: The activity minimum between the end of cycle 23 and the beginning of cycle 24 was the longest and deepest since at least the beginning of the 20th century. This has led to speculation that the Sun is changing its behaviour. The sunspot number and 10.7-cm solar radio flux indices have traditionally been highly correlated, so a change in the relationship between them might flag at such a change. An examination of this relationship suggests a significant change in the relationship between activity in the photosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…Relative to the solar cycle 22-23 minimum, the SEM UV fluxes were 10% lower and the MgII core-to-wing ratio, a key proxy for the chromosphere and low corona, was 10% lower, an unprecedented level Solomon et al 2010Solomon et al , 2011Woods 2010b;Lean et al 2011a). Tapping & Valdés (2011) also show a drop of the minimum F 10.7 radio flux below the average of the four previous minima, but it is comparatively small (3%).…”
Section: Introductionmentioning
confidence: 67%
“…Relative to the solar cycle 22-23 minimum, the SEM UV fluxes were 10% lower and the MgII core-to-wing ratio, a key proxy for the chromosphere and low corona, was 10% lower, an unprecedented level Solomon et al 2010Solomon et al , 2011Woods 2010b;Lean et al 2011a). Tapping & Valdés (2011) also show a drop of the minimum F 10.7 radio flux below the average of the four previous minima, but it is comparatively small (3%).…”
Section: Introductionmentioning
confidence: 67%
“…He concluded that the calibration of F 10.7 can be traced through the entire time series and is not drifting to higher values in the current epoch. Tapping and Valdés (2011) showed that several solar-activity indices, especially F 10.7 and R Z , are well correlated at some times and less so at others. They associated these differences with the evolution of solar activity in the different layers of the solar atmosphere.…”
Section: Changes In R Z Calibrationmentioning
confidence: 99%
“…F 10.7 The solar spectral irradiance at a wavelength of 10.7 cm [F 10.7 ] is a well-known index of solar activity, which has been measured on a daily basis since 1947 (Covington, 1969;Tapping and Charrois, 1994). F 10.7 peaks at solar maximum and fades to around 60 × 10 −22 W m −2 Hz −1 ≡ 60 SFU at solar minimum.…”
Section: R Zmentioning
confidence: 99%
“…Several recent studies have shown that F 10.7 and SN were in fair agreement until 1995 but then started to diverge, with the SN falling significantly below F 10.7 after 2000 (Svalgaard and Hudson, 2010;Lukianova and Mursula, 2011;Tapping and Valdés, 2011;Clette and Lefèvre, 2012). Clette et al (2014) already showed that by applying the correction for the Locarno drifts, which precisely cause an underestimate of the SN after 2000, the difference between the two series was cut by about half, but that a significant disagreement was still present for that interval.…”
Section: Inhomogeneities In F 107mentioning
confidence: 99%